Stakeouts and strollers : a mystery - Phillips, Rob, 1981- (Minotaur Books, 2026)
"Amateur private investigator and new dad Charlie Shaw gets more than he bargained for when he agrees to track down a young girl's missing father in Rob Phillips' 2024 Minotaur Books/Malice Domestic Best First Mystery Novel award-winning debut. Charlie Shaw is low on sleep. And cash. Otherwise, life is going pretty well for the ex-crime reporter: he's happily married to his college sweetheart, he's a first-time dad to the most adorable baby girl in existence, and he's making ends meet as a rookie PI. But when Charlie meets Friday Finley, a frightened sixteen-year-old runaway on a stakeout-gone-wrong, his world gets a little more complicated. Friday is looking for her estranged father Shawn, an unreliable alcoholic who left when she was young-and who also happens to be her only shot at avoiding the foster care system since her mother's death a few weeks earlier. At first, Charlie believes the man is simply hiding out somewhere, avoiding his responsibilities as usual, but the more he investigates, the more unsettling-and dangerous-Shawn's disappearance becomes. When his own family is threatened, Charlie realizes he's in over his head, but can he back out now that he's begun to care for Friday as his own? A perfect page-turning blend of humor and high stakes, Stakeouts and Strollers is a heartwarming story of fatherhood, family, and what it really means to be a "Girl Dad.""-- Provided by publisher.